Effect of Cu content on microstructure transformation and mechanical properties of Fe-Al dissimilar laser welded joints. (June 2020) - Chen, Xiaming; Wang, Xiaonan; Liu, Zhenguang; Hu, Zengrong; Huan, Pengcheng; Yan, Qian; Hiromi, Nagaumi
Graphical abstract: Highlights: Higher Cu content was benefit to reducing δ -ferrite, and improving hardness of WS; The microstructure at interface consisted of (Fe, Cu)2 Al5 and (Fe, Cu) Al3 IMC with adding Cu; Higher Cu content was benefit to decreasing the hardness and peak thickness of IMCs layer; The shear tensile strength of the welded joint with 0.3 mm-thick Cu foil was higher than that of direct samples. Abstract: An YLS6000 continuous laser was used to weld DP980 to a 1.5 mm thick A6061, and Cu foil with different thickness was pre-placed at the joint prior. According to this, the effect of Cu content on the microstructure transformation and mechanical properties of the microstructure and the mechanical properties of the Fe-Al laser welded joints were discussed, and summed up in two points: On one hand, a higher Cu content was in favor of generating a weld seam with a low δ-ferrite content, and the microhardness increased from 277 HV to 346 HV. On the other hand, Cu stacked on the surface of the Fe-Al intermetallic compounds (IMCs) and suppressed the interdiffusion of Fe and Al, while also replacing Fe to generate (Fe, Cu)2 Al5 and (Fe, Cu)Al3, which have excellent mechanical properties. Thus, a higher Cu content was beneficial for decreasing the microhardness and thickness of the IMCs layer and improving the shear tensile strength of the welded joints, which was ~7% higher than that of the directly welded samples.